Teaching the Arts in the Primary School Curriculum: What Strategies Imbue the Integrative Arts Subjects? - MANNATHOKO, MAGDELINE C.; MAMVUTO, ATTWELL (Studies in art education, 2018)
This qualitative case study investigated primary school teachers' approaches to the teaching and learning of the arts in eight purposefully sampled infant and junior classes in Botswana and Zimbabwe in 2016. Data were collected over a period of three months. Twenty-four creative and performing arts teachers were observed teaching in the two countries followed by interviews and analysis of curricular documents. The study revealed that most creative and performing arts teachers did not consider the integrated nature of the subjects but taught the disciplines as discrete components. In all of the study sites, teachers displayed limited disciplinary and pedagogical knowledge, skills, and competencies and faced myriad implementation challenges imposed by the already expansive primary school curriculum. This narrative inquiry proffers educational implications for the development and enhancement of arts education policies in the respective countries and ultimately the recognition of the subjects in the primary school curriculum. The implications drawn from the study can be applied to similar art learning contexts beyond the sites the study was situated in as well as teacher education in a broader context.